2010
DOI: 10.2503/jjshs1.79.91
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Nuclear Genome Construction and the Plastome-genome Incompatibility of Progenies from Intra- and Inter-ploid Cross of Evergreen Azaleas × Rhododendron japonicum f. flavum

Abstract: In intersubgeneric crosses of diploid evergreen azaleas (EV) × diploid Rhododendron japonicum f. flavum (JP), many progenies become albino as a result of plastome-genome incompatibility between a plastid genome from EV and a nuclear genome from JP. To clarify the mechanism of the incompatibility, inter-and intra-ploid crosses of diploid (2x) EV × diploid (2x) JP, tetraploid (4x) EV × tetraploid (4x) JP, 2x EV × 4x JP, and 4x EV × 2x JP were conducted. Seeds were obtained in all crosses, although the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Ureshino and Miyajima (2002) reported that a triploid green seedling with 2x and 1x nuclear genomes from evergreen azalea and R. japonicum, respectively, had ptDNA derived from the evergreen azalea. In addition, plastome-genome incompatibility was broken by a relative increase of the gene from evergreen azaleas in the nuclear gene of hybrid seedlings (Ureshino et al, 2010). The mechanism of ptDNA inheritance detected in the cross of R. uwaense #1 × R. yedoense var.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ureshino and Miyajima (2002) reported that a triploid green seedling with 2x and 1x nuclear genomes from evergreen azalea and R. japonicum, respectively, had ptDNA derived from the evergreen azalea. In addition, plastome-genome incompatibility was broken by a relative increase of the gene from evergreen azaleas in the nuclear gene of hybrid seedlings (Ureshino et al, 2010). The mechanism of ptDNA inheritance detected in the cross of R. uwaense #1 × R. yedoense var.…”
Section: Discussionmentioning
confidence: 97%
“…As a more sensitive polymorphic marker, the PCR-SSCP method has been used to detect polymorphism within species or among some closely related species and to investigate the inheritance pattern of ptDNA (Chen et al, 2002;Shiraishi et al, 2001). Furthermore, the PCR-SSCP method has been used to study chloroplast DNA inheritance in azaleas (Itabashi et al, 2008;Ureshino et al, 2006Ureshino et al, , 2010. Therefore, we used this method to clarify ptDNA inheritance.…”
Section: Molecular Analysis Of Hybridity and Plastid Dna Inheritancementioning
confidence: 99%
“…Gray) Kron f. flavum (JP), unilateral genome-plastome incompatibility occurred in F 1 progenies when EV plants were used as seed parent. The majority of the progenies suffered from albinism because of incompatibility between EV-plastids and JP nuclear genome, and green plants occurred only in the case of occasional plastid DNA inheritance from the JP-parent [62]. Crossing of diploids, 2 × EV (genome constitution EE) × 2 × JP (genome constitution JJ) produced albinas with genomic constitution EJ.…”
Section: Genetic Analysis Of Nuclear-plastid Incompatibility In Azaleasmentioning
confidence: 99%